SURFACE CHARACTERISTICS AND BLOOD COMPATIBILITY OF POLYURETHANES GRAFTED BY PERFLUOROALKYL CHAINS - HAN, DK; JEONG, SY; KIM, YH; MIN, BG (VSP BV, 1992)
Polyurethane (PU) surface was chemically modified by grafting of perfluorodecanoic acid (PFDA) to produce a highly hydrophobic surface to compare the blood compatability with hydrophilic poly(ethylene oxide) (PEO) grafted PUs. The advancing contact angle of modified PU-PFDA was increased up to 115 deg, while that of untreated PU was 86 deg. The PFDA grafted PU exhibited less adhesion and shape change of platelets than untreated PU, and the activated partial thromboplastin time (APTT) of PU-PFDA was considerably extended. The ex vivo occlusion time of untreated PU was only 50 min, but that of PFDA grafted PU was extended to 130 min, indicating that this hydrophobic surface is significantly blood compatible. It is interesting to find that the enhanced blood compatibility of very hydrophobic PU-PFDA was equivalent to hydrophilic PU-PEO.
Keywords: HEPARIN-IMMOBILIZED POLYURETHANES